Development of a Serious Game for Ankle Rehabilitation with T-FLEX (2020)
Conventional physical therapy and rehabilitation with robotic devices effectively improve the sequelae and restore function for stroke survivors. However, repetitive exercise therapy may cause a lack of interest and demotivation which decreases the therapy success. Hence, the inclusion of feedback strategies, like serious games, has proven to be a significant improvement in these areas. This project introduces the development and preliminary validation of a serious game in assisted neurorehabilitation with the T-FLEX ankle exoskeleton after stroke. To accomplish this, a literature review of documents focused on motor learning and cognitive rehabilitation was developed. The design principles included rewards, challenges, clear objectives, a calibration stage, and evaluating performance methods. Following this, a serious game controlled by plantar and dorsal flexion movements to evade enemies was developed. The implementation of each strategy allowed to develop a complete platform that included all the criteria studied for therapy. The game was assessed in a unique healthy participant considering two conditions: with and without wearing T-FLEX. The usability evaluation was performed through the game results and surveys. In terms of the game results, an average precision greater than 95% could be observed. Besides the participant exhibited a positive perception and high adaptation to the interface. In this way, the game proved to represent an attractive tool to be potentially used in ankle rehabilitation after a stroke. Nevertheless, it is necessary to assess its response in healthy participants and stroke survivors to evaluate the impact of the strategy and corroborate what was found in this study.